COMMUNITY DEVELOPMENT PENANGANAN WABAH PMK BERBASIS KEARIFAN LOKAL DI DESA SUMBUNG, KECAMATAN CEPOGO, KABUPATEN BOYOLALI - Slamet Haryanto; Purbudi Wahyuni; Jaka Purwanta; Johan Danu Prasetya; Teddy Agung Cahyadi (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2023)
Sumbung Village is located in Cepogo District, Boyolali Regency, precisely on the east side of the Merapi Slope and is located about 10 km from the center of the capital Boyolali Regency is a milk-producing dairy cattle center because the number of female cattle farmers in the Sumbung Village community is very large, the majority of livestock are cattle cattle FMD outbreak. Sumbung Village supports the economy of the local community, even the Boyolali Regency government itself. When the FMD outbreak spread in Sumbung Village, farmers suffered losses of up to 80%. The impact of FMD Outbreak in Sumbung Village is very heavy, but with the ability of local resources and local wisdom owned by the Sumbung Village Community, they can carry out FMD outbreak handling, especially in the treatment and recovery after FMD Outbreak. Through the research method to be used in this study using a qualitative approach with the PRA (Participatory Rural Appraisal) method. Research Involving all actors of the Sumbung Village community who play an active role in handling FMD outbreaks at the community and government levels, it was found that the Community Development carried out by the people of Sumbung Village was very good in handling FMD outbreaks, especially the use of traditional medicinal plants around their homes. Local wisdom with the use of medicinal plants is a form of empowerment of the people of Sumbung Village in handling FMD outbreaks independently.The actions of the Sumbung Village Community in handling FMD Outbreak by planting medicine.This good learning can be used as a guide in handling emergency situations in the future.